2007
DOI: 10.1111/j.1365-2265.2007.03097.x
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine treatment for benign thyroid disorders: results of a nationwide survey of UK endocrinologists

Abstract: There remain significant differences in several aspects of clinical practice relating to the use of radioiodine treatment for benign thyroid disorders in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 46 publications
2
51
0
1
Order By: Relevance
“…In 2000, Escobar-Jiménez et al 4 surveyed endocrine units in Spain to explore their management of uncomplicated Graves' disease and relapsed patients looking at factors that influenced their decision-making. Vaidya et al 5 reported on a UK survey of 698 clinicians in the year 2008, but the study focused primarily on the use of radioiodine with little information regarding surgical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Escobar-Jiménez et al 4 surveyed endocrine units in Spain to explore their management of uncomplicated Graves' disease and relapsed patients looking at factors that influenced their decision-making. Vaidya et al 5 reported on a UK survey of 698 clinicians in the year 2008, but the study focused primarily on the use of radioiodine with little information regarding surgical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Several surveys of clinicians involved in the treatment of TED have shown wide variability in clinical practice and deficits in the management of TED (8)(9)(10)(11)(12). To address these deficits and improve the outcomes for patients with TED, the European Group on Graves' Orbitopathy (EUGOGO) has recently published a consensus statement on the management of TED (13).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lower liver toxicity thiamazole (TMZ) is usually preferred ). The suboptimal remission rate with thionamide therapy (Allahabadia et al 2000;Vaidya et al 2008) led about 20% of endocrinologists in the UK and 70% in the US to offer radioiodine therapy as primary treatment (Wartofsky et al 1991). In women desiring pregnancy radioiodine is not first choice, since TSH-R-ab tend to persist longer after radioiodine therapy (compared with medical therapy and surgery) and women thus incur a greater risk of foetal/ neonatal hyperthyroidism (Laurberg et al 2008).…”
Section: Graves' Diseasementioning
confidence: 98%
“…The remission rate of Graves' disease under thyrostatic therapy is 50% or less, and significantly higher in women as compared to men (40 vs. 19.6%) (Allahabadia et al 2000;Vaidya et al 2008). Unfavourable prognostic factors are familiar predisposition for autoimmune diseases of the thyroid gland, younger age, male gender, smoking, stressful life events, problems with coping, severe hyperthyroidism (in initial lab), high triiodothyronine/thyroxine (T3/T4) ratio, a long time delay from the onset of symptoms to start of therapy, large goiter, presence of ophthalmopathy or dermatopathy, presence of nodules, high TSH-R-ab titre at onset or end of thionamide therapy as well as high intrathyroidal blood flow at the end of therapy (Allahabadia et al 2000;Heged€ us 2009).…”
Section: Thionamide Therapy and Remission Rate Of Graves' Diseasementioning
confidence: 98%